Governance Structure and the Credibility Gap: Experimental Evidence on Family Businesses’ Sustainability Reporting - Hsueh, Josh Wei-Jun (2018)
This paper examines the success of corporate communication in voluntary sustainability reporting. Existing studies have focused on the perspective of the communicators but lack an understanding of the perspective of information recipients to clearly evaluate this interactive communication process. This paper looks at the issue of a credibility gap perceived by external stakeholders when they doubt the authenticity of communicated information due to the reporting company’s governance structure. The paper uses family businesses to exemplify the emergence of such a gap when outsiders become concerned about the potential agency problem of the integrated ownership and management controlled by a few members of the same family. Following source credibility theory, these concerns raise a credibility gap associated with a family firm’s trustworthiness and goodwill, even if the family has the expertise to carry out sustainability reporting. The findings of two experimental studies indicate that family businesses suffer a greater credibility gap than non-family businesses. An external and independent assurance service can mitigate such gaps, especially when the service is comprehensive and targets family businesses. The paper provides a complete view evaluating corporate communication by looking at the interaction between the communicating company and the information recipients.
Keywords: Sustainability reporting; Governance structure; family business; External stakeholder; credibility gap; Assurance